Avaliação Nutricional das folhas de Moringa oleífera para aves - Marinho, Jéssica Berly Moreira (2016)
Moringa oleifera leaves are considered a promising food for the Northeast because of its nutritional profile and its ability to be keeping green during periods of drought. The research objective was to evaluate the physical and chemical composition and digestibility and energy value of sheets of dried moringa for birds. The chemical analyzes were carried out for crude protein, dry matter, ether extract, neutral detergent fiber and acid detergent fiber, ash and gross energy by the conventional method and the next spectrometry method of infrared. In the measurement of chlorophyll and the main bioactive compounds such as anthocyanins, total carotenoids, flavonoids yellow, total extractable polyphenols and vitamin C through the spectrometric method. The results of the composition of the dried leaves of the Moringa showed that it has good crude protein (30.93%) for conventional analysis and analysis in NIRS (31.64%) anthocyanins (1.02 mg / 100g), carotenoids total (1.48 mg / kg), chlorophyll (120.62 mg / kg), yellow flavonoids (25.76 mg / 100g), polyphenols (105.15 mg / 100g), especially the amount of vitamin C (485.71 mg / 100g). In the digestibility trial, 20 adult birds were housed individually in cages adapted for excreta collection, with five treatments (0, 5, 10, 15 and 20% inclusion of moringa leaves), distributed in a completely randomized design. For apparent digestibility of diets with increasing levels of inclusion of dehydrated leaves of Moringa oleifera was observed a decreasing linear effect for mineral matter (MM)), y = 27.3120 - 0,4934x, (R2 = 0.65) , ether extract (EE), y = 87.3124 - 0,9394x, (R2 = 0.72); neutral detergent fiber (NDF), y = 29.6686 - 0,2957x, (R2 = 0.61); acid detergent fiber (ADF), y = 20.2322 - 0,1688x, (R2 = 0.68); for the metabolization coefficient of gross energy (GE), y = 72.4564 - 0,4285x, (R2 = 0.77) and apparent metabolizable energy of feed (EMA) y = 3783.96 - 15,52x ( R2 = 0.29). With exeção of dry matter (DM) and crude protein (CP), that no significant effects. The value of apparent metabolizable energy of moringa leaves for adult birds was 2.155,81kcal / kg, a value obtained by Matterson technique. Also the coefficient of energy metabolism (CME) with 47.44% for moringa leaf was observed